2020
DOI: 10.1093/cvr/cvaa016
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor-regulated tyrosine kinase substrate is essential for endothelial cell polarity and cerebrovascular stability

Abstract: Aims Hepatocyte growth factor-regulated tyrosine kinase substrate (Hgs), a key component of the endosomal sorting complex required for transport (ESCRT), has been implicated in many essential biological processes. However, the physiological role of endogenous Hgs in the vascular system has not previously been explored. Here, we have generated brain endothelial cell (EC) specific Hgs knockout mice to uncover the function of Hgs in EC polarity and cerebrovascular stability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“… 46 , 65 , 66 HGF stimulates endothelial cell proliferation and migration through its specific receptor cellular-mesenchymal epithelial transition factor (c-Met) and promotes angiogenesis. 49 TGF-β1 has a dual effect on angiogenesis ( Fig. 1B ), when TGF-β1 binds to activator receptor like kinase 1 (ALK1) and induces recombinant mothers against decapentaplegic homolog 1/ recombinant mothers against decapentaplegic homolog 5(SMAD1/SMAD5) phosphorylation, resulting in angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 , 65 , 66 HGF stimulates endothelial cell proliferation and migration through its specific receptor cellular-mesenchymal epithelial transition factor (c-Met) and promotes angiogenesis. 49 TGF-β1 has a dual effect on angiogenesis ( Fig. 1B ), when TGF-β1 binds to activator receptor like kinase 1 (ALK1) and induces recombinant mothers against decapentaplegic homolog 1/ recombinant mothers against decapentaplegic homolog 5(SMAD1/SMAD5) phosphorylation, resulting in angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al 49 Connective tissue growth factor (CtgF) Promotes platelet adhesion, leukocyte migration and angiogenesis, and regulates collagen synthesis.…”
Section: Mechanisms Of Prpmentioning
confidence: 99%
“…On the basis of the list of differentially abundant metabolites found in each comparison, there were 5 and 16 differential metabolites that were specifically identified in Phases D1 and D3D7 when compared with D0 (Figure 5a), and they were mainly involved in tryptophan metabolism and tyrosine metabolism (Supporting Information: Supplemental Figure 2). Studies demonstrated that tryptophan metabolism was potentially involved in the stress response (Le Floc'h et al, 2011) and tyrosine metabolism was associated with energy metabolism (Yu et al, 2021). An overview of the pathway analysis revealed that the DLS vascularization was accompanied by a series of changes in metabolism, which contributed to the different biological activities of the specific phase.…”
Section: Resultsmentioning
confidence: 99%
“…HGS (hepatocyte growth factor-regulated tyrosine kinase substrate) is involved in tight junction protein trafficking and ECs permeability [ 39 ]. HGS is necessary for maintaining cerebrovascular stability [ 40 ]. PDGFB (platelet-derived growth factor subunit B) is expressed at a very low level in healthy vessels [ 41 ].…”
Section: Discussionmentioning
confidence: 99%